(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Glomerulonephritis, also known as glomerular nephritis, is a group of kidney disorders characterized by inflammation of the glomeruli - the tiny filtering units in the kidneys. While glomerulonephritis can affect individuals of all ages, it is particularly significant in children due to its potential long-term consequences if left untreated.